Faktor Faktor Yang Berhubungan Dengan Kejadianpneumonia Pada Balita Di RSUD Depati Hamzah Pangkalpinang Tahun 2024 - Luthfi Handayani; Indri Puji Lestari; Nurwijaya Fitri (PT. Hasba Edukasi Mandiri, 2025)
Pneumonia is currently still a problem in the health sector where the death rate is still high. Not only that, the prevalence of pneumonia is also increasing both locally, nationally, and even internationally. The increase in the incidence of pneumonia can be caused by factors such as history of vitamin A, BBLR and nutritional status The purpose of this study is to find out the factors related to the incidence of pneumonia in toddlers at Depati Hamzah Pangkalpinang Hospital in 2024. This study uses a sectional study sross design. The population in this study is 608 pneumonia patients at Depati Hamzah Pangkalpinang Hospital in 2023. The sample size in this study was 88 respondents who were selected with the Purposive Sampling Technique. Data analysis using the Chi-square test. The results of this study prove that there is a relationship between the factors of vitamin A (p-value=0.000), BBLR (p-value-0.000), and Nutritional Status (p-value=0.000). With the incidence of pneumonia at Depati Hamzah Pangkalpinang Hospital in 2024. It is hoped that Health Service Institutions can increase the frequency of Health Education to the community to always maintain clean and healthy living behaviors and prevent the occurrence of pneumonia in toddlers.